Repetitive DNAs: the ‘invisible’ regulators of insect adaptation and speciation - Cabral-de-Mello, Diogo C [UNESP]; Palacios-Gimenez, Octavio M (Elsevier, 2025)
Like other eukaryotes, insect genomes contain a large portion of repetitive sequences, particularly transposable elements and satellite DNAs. This review highlights key studies on repetitive DNAs and examines their structural, functional, and evolutionary impact on insect genomes. Repetitive sequences promote genetic diversification through mutations and large-scale rearrangements, playing a crucial role in shaping genomic architecture, aiding organismal adaptation, and driving speciation. We also explore the influence of repeats in genome size variation and species incompatibilities, along with their contribution to adaptive phenotypes and gene regulation. Studying repetitive DNA in insects not only provides insights into basic genomic features but also offers valuable information for conservation strategies, pest control, and advancements in genetics, ecology, and evolutionary biology.